IMPLEMENTATION OF ARTICLE 64 PARAGRAPH (1) LAW NUMBER 22 OF 2009 CONCERNING ROAD TRAFFIC AND TRANSPORT FOR RICE MILL CAR IN DISTRICT OF PONOROGO - ALVIN LINTANG KARSA (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
The provisions concerning the approval of vehicles to be allowed path has been set in the LawNo. 22 Year 2009 on Road Traffic and Road Transportation. In Article 64 Paragraph (1) statesthat every motor vehicle must be registered. Today in Ponorogo, there are new types of motorvehicles are driven without any prior registration process. The vehicle called rice mill car. Policehave not been able to implement this registration rule because there are no special regulations forrice mill car in Ponorogo. These regulations may contain about the type of test that later allowedthe vehicle to be driven on the road.Key Word: Registrastion, vehicles.